2016
DOI: 10.1007/s10856-016-5799-x
|View full text |Cite
|
Sign up to set email alerts
|

Poly(Vinylidene Fluoride-Trifluorethylene)/barium titanate membrane promotes de novo bone formation and may modulate gene expression in osteoporotic rat model

Abstract: Osteoporosis is a chronic disease that impairs proper bone remodeling. Guided bone regeneration is a surgical technique that improves bone defect in a particular region through new bone formation, using barrier materials (e.g. membranes) to protect the space adjacent to the bone defect. The polytetrafluorethylene membrane is widely used in guided bone regeneration, however, new membranes are being investigated. The purpose of this study was to evaluate the effect of P(VDFTrFE)/BT [poly(vinylidene fluoride-trif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 31 publications
2
16
0
11
Order By: Relevance
“…Histomorphometric results revealed that the mean values of bone neoformation between sham and ovariectomized groups were similar, without statistical significance. These data are in agreement with previous results obtained by our group research (Scalize et al, 2016), despite the high mean values obtained for bone Int. J.…”
Section: Discussionsupporting
confidence: 94%
“…Histomorphometric results revealed that the mean values of bone neoformation between sham and ovariectomized groups were similar, without statistical significance. These data are in agreement with previous results obtained by our group research (Scalize et al, 2016), despite the high mean values obtained for bone Int. J.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, we selected the PVDF-TrFE/BT membrane due to its good in vitro biocompatibility and the capacity to induce bone formation in both normal and osteoporotic rats and decrease bone resorption by inhibiting osteoclastogenesis. 8,29,30,31,32,33 In addition, in a previous study, the PVDF-TrFE/BT membrane was successfully combined with osteoblast injections to increase the amount of bone formation in the calvarial defects of normal rats. 11 For bone regeneration based on the use of cells, several tissues have been investigated as cell source; however, the bone marrow still remains the most common source, at least in part, due to its ease of accessibility and multilineage differentiation potential.…”
Section: Discussionmentioning
confidence: 99%
“…The PVDF-TrFE/BT membrane was used as it can promote bone formation in both normal and osteoporotic rats. 8,11 The defect size was selected based on previous studies where no significant bone formation was observed even 12 weeks post-surgery. 15,16 Two weeks postimplantation, the animals were randomly distributed to receive local injections of 50 µl of PBS (Gibco-Invitrogen) containing 5 × 10 6 MSCs collected from healthy rats (n = 5) or 50 µl of PBS without MSCs (Control, n = 5).…”
Section: In Vivo Bone Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Circular bone defects of 5 mm in the calvaria in adult rats were performed in this study as reports show that such defects provide an adequate model for evaluating bone neoformation in the craniofacial region . The experimental period of 30 days in this study was chosen in line with other reports . During this period a layer of osteoblasts on neoformed bone from irradiated animals was observed, while in the irradiated animals only non‐calcified connective tissue was present.…”
Section: Discussionmentioning
confidence: 99%